PENINGKATAN KETERAMPILAN MENYIMAK CERITA MENGGUNAKAN MODEL PAIRED STORYTELLING BERBANTUAN MEDIA WAYANG PADA SISWA SEKOLAH DASAR - Renjani, Syahlini ersa dwi; Hafizah (Educational Journal of Bhayangkara, 2024)
The aim of this research is to use story listening skills using a paired storytelling learning model assisted by wayang media in Class IV at SDN Bekasi Jaya I Bekasi City. Classroom Action research or PTK approach was established in constructing this study. The kemmis model is also Mc. Taggart which includes planning, implementation, observation and reflection stages with the subject of 31 students was applied as the research design. In collecting data, observation and documentation methods were applied using descriptive data analysis, including qualitative and quantitative.  The study findings illustrate that story listening skills using the paired storytelling learning model assisted by wayang media are increasing, namely in cycle I by 73.8%, then in cycle II it has increased by 90.7%. Thus, the findings from the research are that the application of the paired storytelling model which utilizes wayang media has a positive effect on the development of narrative listening skills which also increases the learning participation of students in Class IV at SDN Bekasi Jaya I Bekasi City.